Analysis of the Perception of Conflict and Its Positive Resolution in University Students - José Ángel Martínez-López; Jerónimo Molina Cano; Pilar Munuera Gómez; Ana Maria Costa e Silva (Social Sciences, 2022)
This research aimed to analyze the perception of conflict in universities and the ways of dealing with it in relation to the 17 Sustainable Development Goals of the United Nations. The research was developed from a quantitative approach in three universities in two European countries: the University of Murcia and Complutense University of Madrid (Spain) and University of Minho (Portugal). The sample consisted of 247 university students and the technique used was an ad hoc survey administered online. Among the main research results we can highlight that (a) the perception of conflict is mostly negative; (b) there are predictive variables in the positive view of conflict; and (c) university students clearly identify the peaceful resolution of conflicts with some of the Sustainable Development Goals. The main conclusions are that conflict is inherent to any organization and the university must be sensitive to the conflicts that occur within it. It is therefore necessary to create intra-university mediation services as a conflict resolution resource for the entire university community. Training and a positive view of conflict favors the construction of a citizenry capable of dialogue and of resolving the conflicts that arise in their adult life.